Analysis of Nursing Care in Adolescents with Anemia with the Application of Monitoring and Education Interventions for Giving Blood Added Tablets at Teluk Dalam Health Center Banjarmasin - Eka Rani Norlailasari; Mariani Mariani; Evy Noorhasanah (CV. Rayyan Dwi Bharata, 2023)
Young women, who tend to become mothers will be more affected by anemia because they tend to get pregnant and give birth. blood supplement tablet supplementation program for young women, one of the government's efforts to ensure adequate iron intake to prevent anemia. Before administering Blood Supplement Tablets, adolescents should be given information about anemia in Blood Supplement Tablets, as well as guidance or supervision during the administration of Blood Supplement Tablets. The purpose of this research is to describe the results of monitoring and educating the administration of blood supplement tablets. The writing method is in the form of case studies on adolescents with anemia. The results of this case study showed an increase in hemoglobin and hematocrit levels. The control card is filled in according to the date of taking the medicine and signed by the parents. With this case study, it is hoped that nursing interventions related to the method of increasing hemoglobin levels in young women with anemia can be developed.